HOPELESSNESS ANALYSIS OF FEMALE PRISONERS IN TERMS OF THE CRIMINAL PERIOD SERVED AND THE INTENSITY OF FAMILY VISITS - Trisna, Rina; Zikra, Zikra (Jurnal Neo Konseling, 2020)
Hopelessness is a state of helpless individuals who lose hope about their future. This study aims to describe hopelessness and see the the difference in terms of the criminal period served and the intensity of family visits on female prisoners in LPKA class IIB Payakumbuh. This research uses a comparative descriptive approach. Research subjects in this study were 32 female inmates. The research instrument was a questionnaire about hopelessness with a Likert scale model. Data were analyzed using variance analysis technique (ANAVA). The results showed : (1) Hopelessness of female convicts based on the criminal period underwent namely in the 0-1 year period was in the high category, in the 1-2 year period was in the high category, and >3 years was in the high category, and there were no differences the significant hopelessness of female convicts in terms of the criminal period served. (2) Hopelessness of female prisoners based on the intensity of family visit in the never visited are in the high category, in the group rarely in the very high category, and in the group often in the very high category, and there is no significant difference in the hopelessness of female prisoners in terms of the intensity of family visits. (3) There is no hopelessness of female prisoners in terms of the criminal period served and the intensity of concurrent family visit. Therefore we need guidance and counseling services to help alleviate hopelessness and parent support for female prisoners.